2020
DOI: 10.1177/2048872620930509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of timing of intraaortic balloon counterpulsation on mortality in cardiogenic shock – a subanalysis of the IABP-SHOCK II trial

Abstract: Background Conflicting results exist on whether initiation of intraaortic balloon pumping (IABP) before percutaneous coronary intervention (PCI) has an impact on outcome in this setting. Our aim was to assess the outcome of patients undergoing IABP insertion before versus after primary PCI in acute myocardial infarction complicated by cardiogenic shock. Methods The IABP-SHOCK II-trial randomized 600 patients with acute myocardial infarction and cardiogenic shock to IABP-support versus control. We analysed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Studies exploring the use of IABP do not demonstrate a consistent relationship between timing of device initiation and survival in PCI for AMICS. Some of these studies illustrate no association between timing of IABP initiation and survival, [28][29][30][31] while results from a retrospective cohort study suggested that only pre-PCI IABP may improve survival. 32 Other studies comparing IABP to Impella include limitations that may yield different conclusions once reconciled.…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring the use of IABP do not demonstrate a consistent relationship between timing of device initiation and survival in PCI for AMICS. Some of these studies illustrate no association between timing of IABP initiation and survival, [28][29][30][31] while results from a retrospective cohort study suggested that only pre-PCI IABP may improve survival. 32 Other studies comparing IABP to Impella include limitations that may yield different conclusions once reconciled.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences between patient survival and death according to the timing of counter-pulsation insertion, similar to a study that aimed to evaluate the outcomes of patients undergoing IABP insertion before vs. after primary PCI in acute myocardial infarction that were complicated by cardiogenic shock. The analysis included 275 patients, and the timing of IABP implantation before or after primary PCI did not affect the outcomes in these patients [ 15 ]. In large randomized controlled trials in patients with acute coronary syndrome (ACS) and high-risk percutaneous coronary intervention (PCI), there was no benefit of IABPs in reducing the infarct size and no difference in major adverse cardiac and cerebrovascular events (MACCE) between patients undergoing high-risk PCI, either with or without IABP support.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of MCS device insertion may be critical in certain clinical situations. 9,10 In AMI-CS, MCS devices should be inserted as soon as possible if the initial resuscitative attempts with conventional pharmacological support fail, and preferably before PCI. 11 This was explored in a multidisciplinary team-based protocol, the National Cardiogenic Shock Initiative, which used a standardized treatment algorithm to improve the effectiveness of MCS devices in AMI-CS.…”
Section: Rationale For Use Of Mechanical Circulatory Supportmentioning
confidence: 99%